2001
DOI: 10.1007/s004040000100
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of dilatation and curettage for abnormal uterine bleeding

Abstract: Dilatation and curettage was performed under anesthesia in outpatients in 1,837 patients aged over 26 with a history of abnormal uterine bleeding not associated with pregnancy or ovulation. Fifty-one (2.8%) patients were found to have malignant disease. Of these, 47 patients had endometrial carcinoma. An additional 111 (6.0%) patients were found to have endometrial hyperplasia. The incidence of either malignant disease or endometrial hyperplasia was 9.7% in patients over the age of 40. Complications of this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
14
1
1
Order By: Relevance
“…Curetting is still the standard procedure for evaluating endometrial lesions such as carcinoma and hyperplasia, but this procedure has several deficiencies. Besides of its tendency to cause pain and injury, as well as its cost (Tabata et al 2001), curetting can only evaluate less than half of the uterine cavity in approximately 60 % of dilatation and curettage (D&C) procedures, which can result in false-negative diagnoses (Kipp et al 2008). Therefore, there is an urgent need for alternative devices which can be used for early detection of endometrial lesions, especially carcinoma and its precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Curetting is still the standard procedure for evaluating endometrial lesions such as carcinoma and hyperplasia, but this procedure has several deficiencies. Besides of its tendency to cause pain and injury, as well as its cost (Tabata et al 2001), curetting can only evaluate less than half of the uterine cavity in approximately 60 % of dilatation and curettage (D&C) procedures, which can result in false-negative diagnoses (Kipp et al 2008). Therefore, there is an urgent need for alternative devices which can be used for early detection of endometrial lesions, especially carcinoma and its precursors.…”
Section: Introductionmentioning
confidence: 99%
“…While other studies showed dilatation and curettage is an inadequate diagnostic and therapeutic tool for all uterine disorders, this technique missed 62.5% of major intrauterine disorders, and all endometrial disorders were still present in the removed uterus 15 . In other study 16 showed 2.5% of the patients were found to have endometrial carcinoma with median age 56.6 years and 6% of the patients were found to have endometrial hyperplasia whose age was 47.7years, of those 3.6 % had simple hyperplasia and 2.4% complex hyperplasia 16 , while in this study 2 out of 275 (0.73 %) of the patients were found to have endometrial carcinoma and in older than 45 years age group, while 25 out of 275 (9.09%) were found to have endometrial hyperplasia, of those 8.36% had simple hyperplasia and 0.73% complex hyperplasia. The criteria for adequacy and common artifacts in endometrial biopsies, as well as the interpretation of endometrial biopsies in general, may cause problems for pathologists.…”
Section: Figurementioning
confidence: 82%
“…This increase of life expectancy leads to an increasing number of older patients suffering from degenerative disorders. Furthermore, advanced age is associated with an increased morbidity in gynaecology and obstetrics generally [2,3]. One example for an age-related disease is the pelvic organ prolapse leading to recurrent genital ulcerations as well as urinary incontinence occasionally and thus restraining the quality of life [4].…”
Section: Introductionmentioning
confidence: 99%
“…In general, hysterectomy is one of the most frequently done gynaecological major surgical procedures and in up to 90% performed to treat benign diseases [8,9]. However, with advanced age the incidence of endometrial hyperplasia and malignant diseases increases as well [2]. Pre-existing comorbidity is related to the patient's age.…”
Section: Introductionmentioning
confidence: 99%